Peran Kualitas Produk dan Harga terhadap Keputusan Pembelian Tahu Mentah (Studi Kasus pada Home Industri Tahu Bundaran Smekto) - Widiastuti, Wiwit (Universitas Darwan Ali, 2020)
This study discusses the effect of product quality and price on buying decisions of tofu crude (study case of tofu home industry in Bundaran Smekto). The research instrument was an experiment and questionnaire. The sampling technique in this study was purposive sampling with a total sample of 100 respondents. This research uses quantitative methods. Based on the testing of the t-test results obtained, the product quality variable has a t count of 0.020 with a significant 0.025, because the probability <0.05 then H0 is rejected and Ha is accepted. The price variable has a t-count of 0.009 with a significant 0.378. Because probability> 0.05 then H0 is accepted and Ha is rejected. So it can be concluded that product quality variables have a significant effect on purchasing decisions, while prices do not have a significant effect on purchasing decisions.